Stakeholder participation and academic performance: A study among primary schools in Alebtong District, Uganda - Elepu, Catherine; Acanga, Alfred; Mwesigwa, David (American Journal of Education and Learning, 2023)
The overarching goal of this study was to establish the link between stakeholder’s partcicpation in planning, monitoring and implementation of school activities and the academic performance of pupils in Abako Sub County, Alebtong district. The study embraced a cross-sectional survey study design using a mixed methods approach. Structured questionnaires were developed by the researcher for data collection from 142 respondents. Measures of central tendency (Frequency, Percentages, Mean and Standard Deviations) were used to describe the variables while correlation and regression analyses were used to establish the direction and strength of the link between study variables. The findings revealed that stakeholder’s participation in monitoring (p=0.015,β=0.326) and participation in implementation (p=0.23,β=0.334) significantly affect pupils’ academic performance in Abako Sub County, Alebtong district. However conducting monitoring, planning and implementation of activities, by stakeholders, accounts for 63.4% variation of all the possible factors that are likely to account for pupils’ academic performance in Alebtong district (Adjusted R2= 0.634). This study valorizes efforts of school management to promote involvement of parents and other significant stakeholders in the planning, monitoring and implementation of activities as a pathway to enhanced pupil performance.